Chromosome arm-specific BAC end sequences permit comparative analysis of homoeologous chromosomes and genomes of polyploid wheat - Sehgal, Sunish K.; Li, Wanlong; Rabinowicz, Pablo D.; Chan, Agnes; Šimková, Hana; Doležel, Jaroslav; Gill, Bikram S. (My University, 2012)
Background: Bread wheat, one of the world’s staple food crops, has the largest, highly repetitive and polyploid genome among the cereal crops. The wheat genome holds the key to crop genetic improvement against challenges such as climate change, environmental degradation, and water scarcity. To unravel the complex wheat genome, the International Wheat Genome Sequencing Consortium (IWGSC) is pursuing a chromosome- and chromosome arm-based approach to physical mapping and sequencing. Here we report on the use of a BAC library made from flow-sorted telosomic chromosome 3A short arm (t3AS) for marker development and analysis of sequence composition and comparative evolution of homoeologous genomes of hexaploid wheat. Results: The end-sequencing of 9,984 random BACs from a chromosome arm 3AS-specific library (TaaCsp3AShA) generated 11,014,359 bp of high quality sequence from 17,591 BAC-ends with an average length of 626 bp. The sequence represents 3.2% of t3AS with an average DNA sequence read every 19 kb. Overall, 79% of the sequence consisted of repetitive elements, 1.38% as coding regions (estimated 2,850 genes) and another 19% of unknown origin. Comparative sequence analysis suggested that 70-77% of the genes present in both 3A and 3B were syntenic with model species. Among the transposable elements, gypsy/sabrina (12.4%) was the most abundant repeat and was significantly more frequent in 3A compared to homoeologous chromosome 3B. Twenty novel repetitive sequences were also identified using de novo repeat identification. BESs were screened to identify simple sequence repeats (SSR) and transposable element junctions. A total of 1,057 SSRs were identified with a density of one per 10.4 kb, and 7,928 junctions between transposable elements (TE) and other sequences were identified with a density of one per 1.39 kb. With the objective of enhancing the marker density of chromosome 3AS, oligonucleotide primers were successfully designed from 758 SSRs and 695 Insertion Site Based Polymorphisms (ISBPs). Of the 96 ISBP primer pairs tested, 28 (29%) were 3A-specific and compared to 17 (18%) for 96 SSRs. Conclusion: This work reports on the use of wheat chromosome arm 3AS-specific BAC library for the targeted generation of sequence data from a particular region of the huge genome of wheat. A large quantity of sequences were generated from the A genome of hexaploid wheat for comparative genome analysis with homoeologous B and D genomes and other model grass genomes. Hundreds of molecular markers were developed from the 3AS arm-specific sequences; these and other sequences will be useful in gene discovery and physical mapping.
Citation: Sehgal, S., Li, W., Rabinowicz, P., . . . & GIll, B. (2012). Chromosome arm-specific BAC end sequences permit comparative analysis of homoeologous chromosomes and genomes of polyploid wheat. BMC Plant Biology, 12, 1-13. https://doi.org/10.1186/1471-2229-12-64
Keywords: Chromosome arm; BAC; Homoeologous chromosomes; Polyploid wheat; Bread wheat